Development of dengue vaccines - Lim, Chee Siean *; Poh, Chit Laa * (2018)
Background: Dengue virus (DENV) causes up to 390 million infections yearly, of which 96 million are clinically manifested. Approximately 500,000 people with severe dengue require hospitalization each year and there are at least 25,000 deaths among children from Asian and Latin American countries. DENV is endemic in more than 100 countries. Chemical and biological controls have been implemented in targeting Aedes aegypti and Aedes albopictus mosquitoes, but these control practices failed to stem the dengue transmission. As a result, dengue vaccine has become a potential option recommended by WHO to be implemented in dengue endemic regions. Currently, several vaccine candidates are being evaluated in clinical studies. Amongst the vaccine candidates, live attenuated vaccines (LAV) are the furthest along the development pipeline. The most advanced vaccine, CYD-TDV (Dengvaxia) has been licensed in 19 countries. Several other live attenuated vaccines, as well as DNA, subunit, inactivated virus, viral-vectored and subunit-based vaccines, are under development and evaluation in preclinical or clinical studies. Each of the live-attenuated vaccine candidates targets on molecular determinants of virulence in DENV, with the emphasis on attenuating the DENV and inducing a balanced tetravalent immune response against all the four dengue serotypes. Aims: This review presents several different vaccine approaches and their construction strategies, providing an insight into the development of future dengue vaccines such as live attenuated vaccines, DNA vaccines, sub-unit protein vaccines and viral vectored vaccines. Methods: Recent development status of dengue vaccine candidates was reviewed based on the published data and an online registry for clinical trials (ClinicalTrials.gov) which is run by the U.S. National Library of Medicine, National Institutes of Health. Results: Increasing burden of dengue necessitates the development of a safe and efficacious tetravalent dengue vaccine. Various vaccine strategies are being developed for disease prevention, each has its own strengths and limitations. Dengvaxia is a licensed dengue vaccine in 19 countries but it has been suspended in the Philippines in December 2017 due to its potential risks in children <9 years of age and seronegative vaccinees. TDV was able to elicit neutralizing antibodies as well as cross protective T cell responses against all four dengue serotypes and protected mice and nonhuman primates against challenge with wild type DENV. Seroconversion was achieved in both seronegative and seropositive adults and children <1.5 years of age with a single dose. TV003/TV005 was able to elicit multifunctional T cell response in addition to the humoral response. Seroconversion in 90 per cent of seronegative adults was observed with a single dose of TV005. However, eliciting a balanced immune response against all the four dengue serotypes remained the major impediment. Conclusion : Dengvaxia has been launched in 11 countries but it has been withdrawn in the Philippines due to adverse effects in young children. Experimental vaccines such as TDV and TV003/TV005 are live attenuated vaccines which are currently in phase III clinical trials. Continued field trials will further our understanding of immune correlates of protection or risk.